Development of the Value Co-Creation and Monetization Resilience Model in the Vertical Micro-Drama Ecosystem: a Theoretical Study on Paywall Innovation - Ahmad Budi Sulistioyuwono; Eddy Soeryanto Soegoto; Rahma Wahdiniwaty; Adam Mukharil Bachtiar; Irfan Dwiguna Sumitra (Journal of World Science, 2026)
The rapid transformation of digital content consumption toward short-form and vertical video formats has given rise to vertical micro-dramas as a distinct entertainment ecosystem with unique monetization challenges. While prior studies have examined value co-creation and monetization strategies separately, limited attention has been paid to how these two dimensions interact to sustain revenue in highly volatile, attention-driven environments. This study adopts a theoretical research design using a conceptual model development approach based on a systematic synthesis of international and national scholarly literature. Through thematic and comparative analysis, the study identifies key dimensions of value co-creation—engagement, community participation, data-driven feedback, and institutional collaboration—and maps their interaction with diverse paywall innovations, including microtransactions, hybrid advertising models, subscriptions, and access-based partnerships. The findings demonstrate that monetization resilience in vertical micro-drama ecosystems emerges from the dynamic alignment between participatory value creation and adaptive paywall design, rather than from isolated revenue mechanisms. The study contributes a conceptual framework that explains how co-creation processes, when integrated with flexible monetization architectures and contextualized by local market conditions, enable platforms to achieve sustainable revenue under conditions of rapid technological and behavioral change.